Desain Pembelajaran Contextual Teaching and Learning (CTL) Siswa Underachiever pada Topik Statistika - Miftahul Jannah; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2022)
This study aims to give learning alternatives to underachiever students using CTL (Contextual Teaching and Learning) learning strategies to increase learning outcomes and understanding concepts on statistics topics. The development of this learning is done by analyzing the needs of the underachiever students. Performance objective and learning outcomes are adjusted to the instructional event. The results of this study indicate that CTL (Contextual Teaching and Learning) learning is recommended to help underachiever students in improving learning outcomes and understanding concepts on statistics topics.